The Severity of Periodontitis in Elderly Patients with Type 2 Diabetes Mellitus: A Community-Based Study - Utami, Sri; Kusnanto, Hari; Pramono, Dibyo; Oktavia, Nova; Puspita, Sartika (European Journal of General Dentistry, 2024)
Objective Indonesia is one of the top five countries with the highest prevalence of diabetes mellitus (DM). There were 18 million DM patients in 2020, and this number has doubled in has doubled in 2022. The main complication of DM in the oral cavity is periodontitis. Periodontitis and DM have a bidirectional relationship. Controlling the severity of both diseases can improve the quality of life of DM patients. The aim of this study is to determine the severity of periodontitis in older people with type 2 DM.Material and Methods This research is observational with a cross-sectional design. The research subjects were 263 patients aged ≥ 60 years, taken using a purposive sampling technique. The diagnosis and severity of periodontitis were based on the European Federation of Periodontology (EFP) and the American Academy of Periodontology (AAP) with the Centers for Disease Control and Prevention (CDC), using the clinical attachment loss (CAL) and probing depth (PD) clinical parameters. The diagnosis of DM was established by measuring HbA1c. Descriptive statistics was used to describe the distribution of severity of periodontitis.Results In total, 42 people (16%) in this study did not experience periodontitis, and 221 people (84%) experienced periodontitis with 4.5% of the study population suffering from mild periodontitis, 21.3% moderate periodontitis, and 74.2% severe periodontitis. The results of this study indicated that severe periodontitis was the most common category in patients with type 2 DM. Severe periodontitis is the most common type of periodontitis at all levels of age, occupation, and education. It was found most commonly among those aged 60 to 65 years, housewives, and those with elementary education level with moderate or poor oral hygiene.Conclusion Almost all respondents who suffered from type 2 DM experienced periodontitis, severe periodontitis being most common category at all age levels, occupations, education, and oral hygiene status. The severity of periodontitis in this study tended to be due to high HbA1c levels.
Keywords: elderly; type 2 diabetes mellitus; severity of periodontitis